Selected letters of Marianne Moore - Moore, Marianne 1887-1972 (A Borzoi book, 1997)
Marianne Moore's correspondence makes up the largest and most broadly significant collection of any modern poet. It documents the first two-thirds of this century, reflecting shifts from Victorian to modernist culture, the experience of the two world wars, the Depression and postwar prosperity, and the changing face of the arts in America and Europe. Moore wrote letters daily for most of her life - long, intense letters to friends and family; shorter, but always distinctive letters to an ever-widening circle of acquaintances and fans. At the height of her celebrity, she would occasionally write as many as fifty letters a day. Both Moore and her correspondents appreciated the value of their exchange, so that an extraordinary number of letters, approximately thirty thousand, have been preserved.